Determinants of Employee Performance in Law Enforcement Organizations - Andre Febrian; Dinurrahman Dinurrahman; Akhmadi Waridyanto; Rizqi Muhamad Fazri (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study aims to examine the determinants of employee performance in the Criminal Investigation Unit of the Bandung City Police Resort, focusing on the roles of work environment, work competency, and workload. Research Methodology: This study employed a quantitative survey design. Data were collected using structured questionnaires administered to employees of the Criminal Investigation Unit. Data were analyzed using multiple linear regression as a predictive analytical model to identify patterns of association among the variables without implying causal relationships. Results: The results indicate that a supportive work environment is positively associated with employee performance. Work competency also showed a significant and relatively stronger association with employee performance than other variables. In contrast, workload was not significantly associated with employee performance when examined alongside the work environment and work competency. Conclusions: The findings suggest that employee performance in law enforcement organizations is more closely associated with qualitative organizational and individual factors, particularly the work environment and work competency, than with workload intensity alone. Limitations: This study is limited to a single police unit and examines only a specific set of variables. Employee performance may also be associated with other factors not included in this study. Contributions: This study contributes to the public sector human resource management literature by providing empirical evidence of the factors associated with employee performance in law enforcement institutions, offering practical insights for organizational development through workplace support and competency enhancement.